PENGALAMAN PSIKOLOGIS REMAJA GAY PEKERJA SEKS KOMERSIAL DENGAN PERILAKU SEKSUAL BERISIKO TERHADAP PENULARAN IMS DAN HIV - AIDS DI KABUPATEN JEMBER - Azari, Abdul Aziz (Program Studi Keperawatan dan Kesehatan, Sekolah Tinggi Ilmu Kesehatan (STIKES) Bhakti Al-Qodiri, 2019)
One of the most risky behaviors for STD transmission and HIV-AIDS is the rise of commercial sex worker activities among homosexuals. A teenager does commercial sex work because of the urge to fulfill needs, which includesphysiological, social, economic and cultural needs. This study aims to analyze the drive behavior and dramaturgyprocesses in gay commercial sex workers. This study uses a qualitative research design with a phenomenologicalapproach. Participants in this study were 5 people with purposive sampling data collection techniques. Data wereanalyzed using Colaizzi technique. The results of this study found that most of the drive behavior performed by gayadolescents is economic necessity, while the dramaturgy process that occurs is the front stage.